Penerapan Kompres Hangat dalam Menurunkan Nyeri pada Pasien dengan Abdominal Pain Peritonitis di Ruang Asoka RSUD Prof.Dr. Margono Soekarjo Purwokerto - Nurul Arofah; Ikit Netra Wirakhmi (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Peritonitis is an inflammation of the peritoneum that commonly causes acute abdominal pain accompanied by nausea, vomiting, and impaired elimination. Uncontrolled pain requires comprehensive management, including non-pharmacological interventions such as warm compress therapy, which works through vasodilation and muscle relaxation mechanisms. This study aims to describe nursing care for Mr. S with a diagnosis of abdominal pain due to peritonitis and to evaluate the effectiveness of warm compress therapy in reducing pain. This study employed a descriptive case study design using the nursing process approach, including assessment, diagnosis, planning, implementation, and evaluation. The study was conducted from February 2 to 4, 2026, in the Asoka Ward of RSUD Prof. Dr. Margono Soekarjo Purwokerto, involving one respondent who received warm compress therapy for three consecutive days. The results showed that the patient experienced pain with a scale of 7 (0–10), which decreased to 4 on the second day and further reduced to 2–3 on the third day after the intervention. This was accompanied by increased comfort and improved rest. In conclusion, warm compress therapy is effective as a non-pharmacological intervention in reducing pain in patients with peritonitis and can be used as a complementary therapy in nursing care.